49.4k views
3 votes
Determine which answer in the solution set will make the equation true.

3p + 6 = 5p − 12
S: {−9, 0, 9, 18}

A) 18
B) 9
C) 0
D) −9

User Nkcmr
by
4.7k points

2 Answers

3 votes
Solve equation
3p + 6 = 5p - 12
18 = 2p
9 = p

B)9
User Smirkingman
by
4.4k points
3 votes

Answer:

B) 9 {33 = 33}

Explanation:

A) 3p + 6 = 5p − 12

→ 3(18) + 6 = 5(18) − 12

→ 54 + 6 = 90 - 12

→ 60 ≠ 78

B) 3p + 6 = 5p − 12

→ 3(9) + 6 = 5(9) − 12

→ 27 + 6 = 45 - 12

→ 33 = 33

C) 3p + 6 = 5p − 12

→ 3(0) + 6 = 5(0) − 12

→ 0 + 6 = 0 - 12

→ 6 ≠ -12

D) 3p + 6 = 5p − 12

→ 3(-9) + 6 = 5(-9) − 12

→ -27 + 6 = -45 - 12

→ -21 ≠ -57

Hence, option (B) is correct.

User Oleg Sych
by
4.9k points